Appropriate Social Media Platforms Commensurate with the Maturity of Organizations - Hanafizadeh, Payam; Shafia, Sepideh (Journal of Telecommunications and the Digital Economy, 2021)
As digital technologies advance, the digital world is integrated with the real one through various digital platforms. Digital transformation in organizations is essentially based on emerging technologies and social and digital platforms. The purpose of this study is to help organizations choose the appropriate platforms to interact with customers and participate in the digital world in accordance with the maturity they gain in using these digital technologies. The present research, by synthesizing empirical studies on the use of various social platforms in organizations, provides a conceptual map of the relationship between the platform type and the maturity stage of organizations. According to the findings of this study, general social networks are suitable platforms for organizations with the first-stage maturity characteristics. Various social networks and creativity works sharing sites were recognized as suitable for the second stage; and public blogs and educational materials sharing for the third stage. Microblogs, discussion forums, and business networking sites are also appropriate for organizations with the characteristics of stages four and five. Using the findings of this research, organizations will be able to identify a social platform appropriate to their stage of readiness and maturity and make the most out of its benefits.